The Rules of the Game: Local Wage Bargaining and the Gender Pay Gap - Maria Olsson; Oskar Nordström Skans (Institute of Labor Economics (IZA), 2024)
We study how local bargaining institutions affect the within-job gender wage gap among Swedish blue collar workers. Collective agreements with varying degrees of local flexibility tend to cover blue-collar workers across different occupations within the same firm. As a consequence, workers performing the same tasks but in different firms are covered by different agreements. We show that the gender pay gap is substantially reduced in jobs covered by collective agreements that guarantee each worker a minimum pay raise every year. Bargaining constraints have a greater impact on gender equality in settings where females are underrepresented. Effects are smaller in more productive firms as these firms can share rents above the contractual minimum with less constraints, even when formal contracts are rigid. Overall, the results suggest that the specifics of local bargaining institutions can play an important role in shaping gender wage disparities among low-paid workers.
Keywords: J52; J51; J31; J16; 330; gender equality; collective bargaining; unions